Development of Problem Based Eco-website Media on the Topics of Ecosystem to Improve Critical Thinking and Problem Solving Skills - Farisna, Ieva; Isfaeni, Hanum; Sigit, Diana Vivanti (Jurnal Pendidikan MIPA, 2025)
Learning activities that can be applied to students are by providing innovative learning media so that students are encouraged to hone critical thinking skills and problem solving skills. The purpose of this research is to develop PBL based eco-website media on ecosystem material and analyze the improvement of critical thinking and problem solving skills of class X students of SMAN 1 Waringinkurung Serang district. The research method used is educational design research (EDR) using the Hannafin and Peck model which includes three stages. The need assessment stage shows that students need interesting media equipped with the presentation of images, videos, games, there are cases and media can be used anytime and anywhere without burdening smartphone memory. The design stage is carried out product design to produce eco-website media by providing learning material features in the form of images, text, and videos. Cases are available and equipped with activities with the PBL approach, and interesting games are available. The development and implement stage produces PBL based eco-website media that is feasible to use, this is indicated by the acquisition of values given by media and material experts of 88.33% and 89.17%. The results of the small group readability test to students and educators obtained results of 91,80% and 95.83%, so the media is feasible to use in learning biology ecosystem material. The results of the implementation of learning using PBL based eco-website media in the experimental class were analyzed by MANOVA test which proved that PBL based eco-website media used in biology learning can improve students' critical thinking and problem solving skills on ecosystem material. Thus, the media developed, namely PBL based eco-website, is feasible to use and can improve students' critical thinking and problem solving skills on ecosystem material.       Keywords: critical thinking, eco-website, ecosystem, hannafin and peck, manova, problem solving.